Association of dispositional optimism with Life's Simple 7's Cardiovascular Health Index: results from the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) Sociocultural Ancillary Study (SCAS). Issue 3 (22nd March 2018) - Hernandez, Rosalba; González, Hector M; Tarraf, Wassim; Moskowitz, Judith T; Carnethon, Mercedes R; Gallo, Linda C; Penedo, Frank J; Isasi, Carmen R; Ruiz, John Manuel; Arguelles, William; Buelna, Christina; Davis, Sonia; et al.
Abstract : Objectives: Mounting evidence links positive psychological functioning to restorative health processes and favourable medical outcomes. However, very little is known about the relationship between optimism, an indicator of psychological functioning and the American Heart Association (AHA)-defined concept of cardiovascular health (CVH), particularly in Hispanics/Latinos of diverse backgrounds. To address limitations of existing literature, this study investigated the association between dispositional optimism and CVH in a heterogeneous sample of Hispanics/Latinos residing in the USA. Design: Cross-sectional study. Participants and setting: Data were analysed from 4919 adults ages 18–75 of the Hispanic Community Health Study/Study of Latinos parent study and the Sociocultural Ancillary Study. Main outcome measures: Optimism was assessed using the 6-item Life Orientation Test-Revised (range from 6 to 30). AHA classification standards were used to derive an additive CVH score with operationalisation of indicators as Ideal, Intermediate and Poor. The overall CVH score included indicators of diet, body mass index, physical activity, cholesterol, blood pressure, fasting glucose and smoking status. Multivariate linear and logistic regressions were used to examine associations of optimism with CVH (Life's Simple 7), after adjusting for sociodemographic factors and depressive symptoms. Results: Each increase in the optimism total score was associated with a greater CVH score (β=0.03 per unit increase, 95% CI 0.01 to 0.05). When modelling tertiles of optimism, participants with moderate (β=0.24 to 95% CI 0.06 to 0.42) and high (β=0.12, 95% CI 0.01 to 0.24) levels of optimism displayed greater CVH scores when compared with their least optimistic peers. Conclusion: This study offers preliminary evidence for an association between optimism and CVH in a large heterogeneous group of Hispanic/Latino adults. Our study adds scientific knowledge of psychological assets that may promote CVH and suggests a novel therapeutic target for consideration. Future studies are needed to explore causality and potential mechanism underlying the relationship between positive emotion and heart health.